Conveying Message Distortion: A Synchronous and Asynchronous Approach to Effective Aviation Communication Services - Muhammad Hanif Fahmi; Lian Agustina Setiyaningsih; Malikhatul Lailiyah (Universitas Merdeka Malang, 2023)
The study focuses on message distortion in aviation communication services, seen from the problem of using the media both synchronously and asynchronously. In doing so, 65 articlesÂ from reputable international journals, international journals, and accredited national journals were analyzed. The constructivism paradigm involves multidisciplinary information systems, communications, and media services. Excellent service in aviation is hampered by message distortion from customer service and customers exchanging information because communication media is dominated by asynchronous communication. The combination of approaches using synchronous and asynchronous media bridges the problem of message distortion in aviation communication services. Message distortions include physical disturbances, semantic disturbances, cultural and language differences, no feedback, status or position level differences, and information overload between communicators and communicants.Â Â